An evaluation of a professional development program aimed at empowering teachers’ agency for social justice - van Vijfeijken, Marijke; van Schilt-Mol, Tamara; van den Bergh, Linda; Scholte, Ron H. J.; Denessen, Eddie (Frontiers in Education, 2024)
This article reports on an evaluation study of a professional development program to promote teachers’ agency for social justice and educational equality. Despite that teachers are seen as change agents for social justice, few studies have investigated what empowers them to adopt this role. Therefore, we designed a theory of change with seven manifestations of agency for social justice (e.g., being committed and experts, taking initiatives). Fourteen primary school teachers participated, engaging in individual reflections, focus group interviews, and an open-ended questionnaire. Thematic analysis was used to code manifestations of agency such as commitment and initiatives. The results demonstrated an empowered sense of agency among the participants. For example, they displayed heightened awareness of inequalities and a critical stance towards their own actions, school policies, and the education system in relation to educational equality. This study contributes to theoretical knowledge about how a professional development program for experienced teachers can be used to develop agency for social justice. Key factors that supported teachers’ agency included sufficient time and support in the program to familiarize themselves with social justice and educational equality concepts, as well as receiving comprehensive knowledge on practical interventions and dedicated time for discussing their applicability in their own teaching practice.